Systematic design of superaerophobic nanotube-array electrode comprised of transition-metal sulfides for overall water splitting - Haoyi Li (Nature Portfolio, 2018)
Water splitting by nanostructured, abundant catalysts provides a renewable means to make carbon neutral fuels, but the ideal material morphology and composition remain uncertain. Here, the authors prepare superaerophobic, multi-metallic sulfide nanotube arrays as bifunctional water splitting catalysts.